A user profile for information filtering using RFID-SIM card in pervasive network - Osman, A.A.; Mantoro, Teddy (2011)
The appearance of new technologies allows new data processing techniques. Thus, many new data processing techniques make difficult to user to find pertinent information in suitable time, unless knowing what accurately is in search of, where and how getting it. This paper proposes a pervasive network based information filtering system that integrates user profile such as identity, preference and other important data. User profile is embarked in a RFID-SIM card in order to guarantee its privacy, flexibility, mobility and confidentiality. The overall system objectives are privacy, security and providing pertinent information to the user according to his profile at anytime, anywhere, and in any form. The design and implementation of the system is also presented.